Death Scares : How Potential Work-Migrants Infer Mortality Rates from Migrant Deaths - Shrestha, Maheshwor (World Bank, Washington, DC, 2017)
This paper studies how potential work migrants infer mortality rates from incidents of migrant deaths. In the context of migrant workers from Nepal to Malaysia and the Persian Gulf countries, the study finds that the death of a migrant from a district lowers migration outflows in subsequent months. Furthermore, this migration response is stronger when there have been more migrant deaths in recent months. Using relevant elasticities, this study finds that the migration response implies large changes in mortality rates perceived by potential migrants. Models of learning fallacies better explain the observed responses than a standard model of rational Bayesian learning.